Literatura infantil: una herramienta potencial para aprender a leer en niños de segundo grado, escuela de EGB “Dr. Reinaldo Espinosa Aguilar”. - Barrera Villa, Joselyn Fernanda (2024)
The general objective of this research related to Children's literature: a potential tool for learning to read, was to promote reading in second graders through the use of children's literature to enhance the development of communication skills; to meet this objective, three specific objectives were developed, the first was to diagnose the use of children's literature as a teaching resource to improve reading in second graders; the second was to determine how children's literature influences children's reading by applying pedagogical strategies through a proposal for educational improvement; the next objective was: Evaluate the educational proposal to measure the levels of knowledge acquired in relation to the use of children's literature to improve reading. To carry out the present research a descriptive type of research was used with a qualitative approach, quasi-experimental design, during the progress of the research methods were used such as: inductive, deductive, analytical, among the techniques are: The instruments used were: observation form, interview guide, for data collection, the sampling was non-probabilistic, corresponding to twenty-two students and one teacher. It is of great importance to use children's literature because it allows students to learn to read in a fun way. Through the research it became evident that children's literature is a didactic resource that offers multiple benefits, such as the reading habit, which is essential in the development of learning and love for reading.